Māori and the United Nations - Charters, Claire (Resistance: An Indigenous Response to Neoliberalism, 2007)
Resistance: An Indigenous Response to Neoliberalism is a collection of papers from Maori academics, activists and leaders on the connection between global practices of neoliberalism and the diverse forms of Maori resistance that aim to destablize them.Aotearoa is one of the world leaders of neoliberalism. Successive New Zealand governments since 1984 have pursued neoliberal policies with a faith, vehemence and confidence in their success that few other governments appear to possess.At a time when 'capital flows across borders as it has never done before, and multinational companies have bigger budgets than many states have ever had', this book encourages people to look more closely at Maori views as integral and inspiring in a globalizing world.Resistance: An Indigenous Response to Neoliberalism is edited by Maria Bargh. The other contributors are Claire Charters, Moana Jackson, Bridget Robson, Cherryl Smith, Maui Solomon, Alice Te Punga Somerville, Annette Sykes and Teanau Tuiono.
Keywords: UNDRIP; globalisation; neoliberalism; protest; united nations

Chapter 7: Papaki Rua Ngā Tai: Tides of Confluence: Māori and the State - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: UNDRIP; crown policy; government relations; land tenure; law; mana motuhake; sovereignty; tino rangatiratanga; welfare policies

The face behind the law: The United Nations and the rights of indigenous peoples - Jackson, Moana (Yearbook of New Zealand jurisprudence, 2005)
In recent years Maori people have adopted many strategies to protect and advance the well being and visions implicit in the exercise of tino rangatiratanga. Much of that work has been done at home, but an increasing number of Iwi and other Maori organisations are now participating in international affairs that are seen to have some relevance to our lives. They are joining a worldwide movement by Indigenous Peoples to reassert their rights and reclaim their rightful place.
Keywords: UNDRIP; civil Rights; colonisation; crown law; imperialism; international law; international organization; racism; tiriti o waitangi/treaty of waitangi; waitangi tribunal

The rights of indigenous peoples - Charters, Claire (New Zealand Law Journal, 2006)
Keywords: UNDRIP; māori rights; self-determination; tino rangatiratanga

The Rights of Indigenous Peoples: New Zealand and the Adoption of the Declaration on the Rights of Indigenous Peoples - Charters, Claire (2007)
Discusses the New Zealand position on the adoption of the UN Declaration on the Rights of Indigenous Peoples.
Keywords: UNDRIP; international law

Indigenous Participation in Elective Bodies: The Maori in New Zealand - O'Sullivan, Dominic; Xanthaki, Alexandra (International Journal on Minority and Group Rights, 2009)
The article argues that Maori political participation in New Zealand constitutes a positive example of how the current international standards on indigenous political participation can be implemented at the national level. Notwithstanding the weaknesses of the system and the challenges laying ahead, the combination of the Mixed Member Proportional electoral system, dedicated Maori seats and the establishment of the Maori Party have ensured a Maori voice in Parliament and have broadened the possibilities of effective indigenous participation in the political life of the state. Such state practice that implements the 2007 UN Declaration on the Rights of Indigenous Peoples firmly confirms the position of the Declaration within current international law.
Keywords: UNDRIP; elections; electorates; government; indigenous rights; mmp electoral system; political participation; te pāti māori